Ploidy analysis in water yam, Dioscorea alata L., germplasm - Egesi, Chiedozie N.; Pillay, M.; Asiedu, A.; Egunjobi, J.K. (2002)
Poor reproductive development in yams (Dioscorea spp.) has often been attributed to the polyploid nature of the crop. In this study, flow cytometry was used to determine the ploidy level of 53 accessions of Dioscorea alata, mostly from West African countries, Chad and Puerto Rico. Nuclei were isolated from young leaf material and stained with DAPI (4,6-diamidino-2-phenylindole). The nuclear genome size (2C) was measured as an indicator of the ploidy level. Dioscorea rotundata genotypes with known ploidy levels were used as standards. The results showed that the majority of plants were hexaploid (84.9%) with a smaller percentage of tetraploids (15.1%). A higher number of male plants were hexaploid than tetraploids. This is at variance with earlier findings, which reported that hexaploid male plants are rare. Higher ploidy levels were not directly related to sparse or erratic flowering as previously reported as profuse flowering occurred in some male hexaploid accessions. These findings have important implications for yam breeding in relation to yam genetic resources.